Generation of the Narrow Band Digital Modulated Signals Using Quadrature Digital Upconverter - Kovar, Pavel (Radioengineering Society, 2003)
The paper deals with the modern approach to generation of digital modulated signals at intermediate frequency in digital way. The common digital modulator is based on analogue Quadrature modulator. The modern VLSI integrated circuits enable to implement this signal processing method in digital form. Analog and digital approaches are compared in this document. The measurement of narrow band D8PSK modulation signal generated by Quadrature Digital Upconverter is presented in this paper.
Keywords: Digital modulation; DSP; DDS; Quadrature Digital Upconverter; VDL